2012
DOI: 10.1074/jbc.m112.360388
|View full text |Cite
|
Sign up to set email alerts
|

Ras Guanine Nucleotide-releasing Protein-4 (RasGRP4) Involvement in Experimental Arthritis and Colitis

Abstract: Background: Mast cells express RasGRP4, which is a guanine nucleotide exchange factor and diacylglycerol/phorbol ester receptor. Results: A RasGRP4-null C57BL/6 mouse line was created to evaluate the importance of this signaling protein. Conclusion:RasGRP4 participates in experimental colitis and arthritis. Significance: The inactivation of RasGRP4 might be of therapeutic benefit in some inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…We showed that rats with CIA that had received an intraarticular injection of a RasGRP‐4–specific siRNA had significantly improved arthritis and scarce joint destruction, consistent with the recent finding that RasGRP‐4–null B6 mice are resistant to experimental K/BxN arthritis (). Thus, the importance of RasGRP‐4 in a second well‐established experimental arthritis model has now been shown.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We showed that rats with CIA that had received an intraarticular injection of a RasGRP‐4–specific siRNA had significantly improved arthritis and scarce joint destruction, consistent with the recent finding that RasGRP‐4–null B6 mice are resistant to experimental K/BxN arthritis (). Thus, the importance of RasGRP‐4 in a second well‐established experimental arthritis model has now been shown.…”
Section: Discussionsupporting
confidence: 88%
“…The RasGRP‐4+ cells in mouse synovium that are essential in K/BxN arthritis induced by anti–glucose‐6‐phosphate isomerase autoantibodies have not yet been identified. Nevertheless, the finding that experimental arthritis could not be induced in RasGRP‐4–null B6 mice documented for the first time an essential role for this GEF in the effector phase of the IgG/C5a‐mediated murine arthritis model (). In support of these mouse data, we identified defective isoforms of RasGRP‐4 in the peripheral blood mononuclear cells of a subset of patients with RA ().…”
mentioning
confidence: 99%
“…Subsequently, two independent groups generated RasGRP4 deficient mice and examined its role in mast cells development and function. Both groups demonstrated that RasGRP4 is dispensable for mast cell development and maturation (Adachi et al, 2012; Zhu et al, 2012). The Zhang laboratory showed that RasGRP4 deficiency results in impaired FcεRI-dependent mast cell function such as degranulation and cytokines production.…”
Section: Rasgrp2 and Rasgrp4 In Non-oncogenic Settingsmentioning
confidence: 99%
“…The Stevens group investigated the consequences of RasGRP4 deficiency in two inflammation models, which involve mast cells. Interestingly, they show that RasGRP4 knockout mice are protected from DSS (dextran sodium sulfate)-induced acute colitis as well as from one type of experimental arthritis (Adachi et al, 2012). However, since both of these models also involve other cell types of innate and adaptive arms of the immune system, it is difficult to point out which cells are affected (and how?)…”
Section: Rasgrp2 and Rasgrp4 In Non-oncogenic Settingsmentioning
confidence: 99%
“…We then employed these mice in various models. To that end, RasGRP4 is a signaling protein expressed in MCs (20) that controls the release of cytokines and preformed mediators (21). Our inability to induce K/BxN arthritis in RasGRP4-null B6 mice (21) supports the conclusion made in earlier Kit W /Kit W-v mouse studies that synovial MCs release factors that have adverse roles in acute inflammatory arthritis.…”
Section: Introductionmentioning
confidence: 99%